Reduction and follow-up of hospital discharge letter delay using Little's law. (4th January 2019) - Burruni, Rodolfo; Cuany, Beatrice; Valerio, Massimo; Jichlinski, Patrice; Kulik, Gerit
Abstract: Quality problem: As discharge letters (DL) hold important information for healthcare professionals and especially for general practitioners, rapid and efficient finalization is required. We describe a project aiming to reduce DL submission within 8 days in our Urology Department (UD), as required by the local Hospital Board (HB). Initial assessment and choice of solution: A team was built in UD with staff members and one external expert to study the root causes of delayed DL creation and develop sustainable strategies to improve and monitor the process, including habits changing, training and application of Little's Law. Implementation and evaluation: The study started on January 2015 and ended up on March 2016, involving 908 and 616 DL for old and new process, respectively. The new process decreased the average delay of DL completion from 24.88 days to 14.7 days. Standard deviation of total average delay for DL completion fell from 10.1 days to 7.5 days. We identified four steps needed to DL creation and allowed maximum 2 days for every step completion. No additional resources were employed. Lessons learned: We were able to improve the process of DL creation, by analysing its steps and reducing their variability. This can be easily transposed to other medical departments.